Reducing Posttraumatic Stress Symptoms in Maltreated Youth through Relationships - Day, Timothy L.; Kearney, Christopher A. (Journal of Psychology and Psychotherapy Research, 2015)
1. Sense of relatedness and PTSD symptoms were inversely related among maltreated youth; 2. Trust, support, comfort, and tolerance most closely related inversely to PTSD symptoms, but especially tolerance for others; 3. Tolerance related to assertiveness was most closely related inversely to PTSD symptoms; 4. Findings help identify what aspects of resilience may help prevent PTSD symptoms in maltreated youth.